Benefits of gas phase analysis facility using isotopically labelled gases for the understanding of gas–solid reactions: Reactivity of iron and mild steel in O2, CO2 and CO2/O2 environments. (January 2021) - Rouillard, F.; Young, D.J.
Highlights: Gas Phase Analysis (GPA) technique is a powerful technique for understanding the corrosion mechanism of alloys in mixed gases. At 550 °C, mild steel reacts with O2, CO2 and CO2 –O2 gas mixtures to yield differing reaction products. Both 18, 18O2 and 13 C16, 16O2 molecules participate in oxide formation. The oxidation rate of iron is initially controlled almost exclusively by the dissociation rate of adsorbed O2 . Adsorbed CO2 acts mainly by limiting O2 access to the surface. Abstract: Corrosion of iron and mild steel in gas environments at 550 °C was studied by Gas Phase Analysis (GPA) using 13 C 16, 16 O2 and 18, 18 O2 . This technique is shown to be very powerful in identifying gas–metal and gas-gas interactions. Mild steel reacts with O2 to oxidize and decarburise, with CO2 to decarburise but not oxidize, and with CO2 /O2 to oxidize and carburise. Using simple kinetic modeling, it is demonstrated that the oxidation rate of iron is initially controlled almost exclusively by the dissociation rate of adsorbed O2 . In this regime, adsorbed CO2 acts mainly by limiting O2 access to the surface.